If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 4x + 5 = 2 Reorder the terms: 5 + -7x + 4x = 2 Combine like terms: -7x + 4x = -3x 5 + -3x = 2 Solving 5 + -3x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3x = 2 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 2 + -5 -3x = 2 + -5 Combine like terms: 2 + -5 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| 3xy+x-y=1 | | 19+4(2c-3)= | | 100=2(x+11)(x-5) | | 4x+2z=4+3y | | -5x-9=-4x+1 | | -3x-15y-3x+8y= | | 2x+4=5x-x | | sec(x)sec(x)-7=0 | | sex^2(x)-7=0 | | 7x+(-3y)+(-8x)+9y= | | 3x+3(x-7)= | | 2x+5x+3=3-7x | | 5n-3(n-6)=2+3n | | (3x-6)2=36 | | 2x+3z=5+7y | | y^2=-7 | | 3(4y-1)=(5y+.5) | | 3/14/7/10 | | 5y+y=42 | | 5-y-y=15 | | 1/3w-9/5=-1/2 | | 2a+5-(a-7)= | | 4x^2+5(4x^2-x)-3x= | | (2535+-1157x+189x^2+x^3)(x+1.5)=0 | | 4b^2+20b+25= | | 4y+2w=7 | | y/-4=3 | | x+xy+x=9 | | (5x+8)(3y-1)= | | (25x^2)-81=0 | | (13+-6x+x^2)(x+195)=0 | | (4x+5)(5y-4)= |